استراتيجيات تعلم اللغة لدى متعلمي اللغة العربية وأثرها على تحصيلهم اللغوي: دراسة حالة بجامعة مالايا - Nor Hazrul bin Mohd Salleh (Kulliyah of Education, International Islamic University Malaysia, 2017)
Language learning strategies are very important to reach the desired goal of the process of Arabic language teaching and learning. This study aimed at investigating the level of language learning strategies (LLS) employed by students and Arabic language proficiency of students majoring in Arabic language at the University of Malaya's (UM). This study also attempted to examine the language learning strategies in relation to the Arabic language performance. Finally, it sought to explore whether there is any significant difference among students in terms of their fields of studies and gender in using language learning strategies in Arabic language learning. A quantitative research design was employed in this study which utilizing survey outline as a method to collect the data. The sample of the study were the Arabic undergraduate students of all levels (year 1-4), with a total number of 184 students. Strategy Inventory for Language Learning (SILL) developed by Oxford (1990) was used as an instrument for this study. The means and percentages were used to interpret the level of language learning strategies and Arabic language performance. The language learning strategies construct has six underlying dimensions, namely memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. The Arabic language performance was measured by four underlying dimensions which are listening skill, speaking skill, reading skill and writing skill. The descriptive analysis showed that students evaluated themselves at the medium level on those two constructs. Pearson correlation indicated that there is a significant relationship between language learning strategies and Arabic language performance. Multiple regression analysis indicated that there is a significant contribution of language learning strategies to Arabic language performance. T-test showed that there is no significant difference between language learning strategies and students background (i.e gender and field of studies). It is hoped that the results of the study contribute to the improvement of the language learning strategies and Arabic language performance among students. The study also suggests several further studies for the improvement of Arabic language among students.